2006
DOI: 10.17704/eshi.25.1.a77157458q3u7757
|View full text |Cite
|
Sign up to set email alerts
|

The Rush Started Here II: Hard Rock Gold Mining in North Carolina, 1825 to 1864

Abstract: From 1799 until the early 1830s, North Carolina's Piedmont had rich surface and near-surface gold deposits. Land owning farmers were interested in improving their finances through gold mining in the slow seasons. Those unable to work their deposits leased them to neighbors or landless prospectors for additional income. Over this thirty year period, the surface placer deposits were exhausted and ended the casual off-season gold mining. Dabblers and fair-weather farmers turned miners became entrepreneurs who sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…historical mining activity has thus contributed significantly to mercury contamination of numerous streams throughout Victoria (Bycroft et al 1982;McCredie 1982;Tiller 1990;Churchill et al 2004). Similar patterns have been reported from other major centres of nineteenthcentury gold mining, including California (alpers et al 2005;Isenberg 2005;Singer et al 2013), north Carolina (hines & Smith 2006;Lecce et al 2008), nevada (Wayne et al 1996) and new Zealand (Moreno et al 2005), while extensive mercury pollution also resulted from silver mining and processing in both north america and South america during this period (nriagu 1993de Lacerda & Salomons 1998;Strode et al 2009;Robins 2011). By the 1890s, nine-tenths of the gold produced around the world was recovered by the mercury amalgamation process (Birrell 2004).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…historical mining activity has thus contributed significantly to mercury contamination of numerous streams throughout Victoria (Bycroft et al 1982;McCredie 1982;Tiller 1990;Churchill et al 2004). Similar patterns have been reported from other major centres of nineteenthcentury gold mining, including California (alpers et al 2005;Isenberg 2005;Singer et al 2013), north Carolina (hines & Smith 2006;Lecce et al 2008), nevada (Wayne et al 1996) and new Zealand (Moreno et al 2005), while extensive mercury pollution also resulted from silver mining and processing in both north america and South america during this period (nriagu 1993de Lacerda & Salomons 1998;Strode et al 2009;Robins 2011). By the 1890s, nine-tenths of the gold produced around the world was recovered by the mercury amalgamation process (Birrell 2004).…”
mentioning
confidence: 75%
“…as mercury absorbed the gold and impurities it lost fluidity and effectiveness until it became crusty (Lock 1882). When the mercury developed a frosty appearance, miners knew that it was almost saturated with gold (hines & Smith 2006).…”
Section: Gold Mining and Gold Amalgamationmentioning
confidence: 99%
“…The total volume of Hg lost in Victoria ranged between 121 and 585 tons of reported imports [92], resulting in elevated Hg levels in water, sediments, and biota downstream of old gold workings [17,18]. Other studies have reported a significant Hg contamination from the major centers of the 19th century gold mining sites in California [139][140][141], North Carolina [142,143], Nevada [144], and New Zealand [145]. For instance, sedimentary and historic records from the San Francisco Bay region describe a trend of anthropogenic contamination as a direct result of gold-rush-era mining activities during the 19th century [146].…”
Section: Mercury Discharges Into the Environment Due To Past And Pres...mentioning
confidence: 99%
“…North Carolina was significant because the first gold in the United States of America had been discovered there in 1799. Until the Californian gold rush, it supplied the nation's gold and introduced innovative mining practices (Hines & Smith 2006). 34 Braché's visits to these mining regions were presumably during his tenure as a draftsman with the Orange and Alexander Railway Company, for which construction commenced in 1850.…”
Section: In Search Of Goldmentioning
confidence: 99%